A Simplified Procedure for Biologically Oriented Alveolar Ridge Preservation: Clinical and Histological Findings From a Case Report. Issue 4 (18th September 2020) - Pramstraller, Mattia; Farina, Roberto; Simonelli, Anna; Götz, Werner; Trombelli, Leonardo
Abstract : Introduction: A recent systematic review failed to identify one approach for alveolar ridge preservation (ARP) with superior outcomes compared with the others. The present case report presents a novel, simplified technique for ARP, namely the Biologically‐oriented Alveolar Ridge Preservation (BARP), based on socket grafting and sealing. Case Presentation: After extraction of tooth #19, the socket was filled with a collagen sponge up to 4‐5 mm from the most coronal extension of the bone crest (deep collagen layer). A bovine‐derived xenograft was placed on top of the collagen sponge to fill the coronal part of the socket (graft layer). Socket sealing was then performed by placing a collagen sponge over the exposed portion of the graft (superficial collagen layer), and the wound healed by secondary intention. At implant insertion (4 months after ARP), limited reduction in bone width and no vertical change in ridge height were observed. Histological analysis of a biopsy specimen retrieved during implant site preparation showed a gradient ranging from interconnected trabeculae of mature, lamellar bone in the apical portion to cancellous bone incorporating a modest number of remodeled graft granules in the central portion. In the coronal portion, non‐mineralized tissue with sparse isles of newly formed cancellous bone and residual graft granules was found. Conclusion: The present case report indicates that BARP might provide ideal conditions for preserving the pre‐existing alveolar ridge dimensions following tooth extraction while restricting any potential interference of the graft biomaterial with bone healing dynamics to the coronal part of the socket.